2022
DOI: 10.1155/2022/8435133
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bariatric Surgery on Circulating Levels of Lipoprotein (a): A Meta-analysis

Abstract: Background. Obesity, especially severe obesity, is associated with a higher risk of atherosclerotic cardiovascular disease (ASCVD) morbidity and mortality. Bariatric surgery is a durable and effective weight loss therapy for patients with severe obesity and weight-related comorbidities. Elevated plasma levels of lipoprotein (a) (Lp(a)) are causally associated with ASCVD. The aim of this meta-analysis was to analyze whether bariatric surgery is associated with Lp(a) concentrations. Methods. A literature search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
(83 reference statements)
0
7
0
Order By: Relevance
“… 29 Another meta-analysis study on 1551 patients demonstrated a significant reduction of serum LDL levels following bariatric surgery, especially after RYGB. 30 However, Hu et al, in a meta-analysis on 7443 subjects who underwent RYGB and SG, revealed that, in more than 3 years of follow-up, comorbidities such as dyslipidemia and hypertension had not been improved significantly. 31 Also, Coleman and co-workers, in a study of 8265 patients, found lower dyslipidemia relapse in 4 years of follow-up in RYGB versus the SG group (21% vs. 24%).…”
Section: Discussionmentioning
confidence: 99%
“… 29 Another meta-analysis study on 1551 patients demonstrated a significant reduction of serum LDL levels following bariatric surgery, especially after RYGB. 30 However, Hu et al, in a meta-analysis on 7443 subjects who underwent RYGB and SG, revealed that, in more than 3 years of follow-up, comorbidities such as dyslipidemia and hypertension had not been improved significantly. 31 Also, Coleman and co-workers, in a study of 8265 patients, found lower dyslipidemia relapse in 4 years of follow-up in RYGB versus the SG group (21% vs. 24%).…”
Section: Discussionmentioning
confidence: 99%
“…The Lp(a) lowering effect of RYGB, observed in this study, is in accordance with results from previous studies. A recent meta-analysis including 13 studies and 1551 adults and adolescents revealed a significant decrease in circulating Lp(a) following different types of bariatric surgery (standardized mean difference; -0.438, 95% CI: -0.702, -0.174) [ 8 ]. The heterogeneity between the studies was, however, large, and the mean (SD) Lp(a) levels at baseline ranged from 14.0 (3.65) to 258.2 (378) nmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…7 Unit for Cardiac and Cardiovascular Genetics, Oslo University Hospital, Oslo, Norway. 8 Department of Cardiology, Akershus University Hospital, Lørenskog, Norway.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bariatric surgery is a surgical treatment primarily for obese patients, which improves metabolic and inflammatory processes as well as cardiometabolic risk factors beyond weight loss [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The types of bariatric surgery are sleeve gastrectomy (SG), laparoscopic adjustable gastric band (LAGB), Roux-en-Y gastric bypass (RYGP), biliopancreatic diversion/duodenal switch (BPD/DS), and one anastomosis gastric bypass/mini gastric bypass (OAGB/MGB) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%